(untitled) (Anclajes, 2017)
This paper focuses on the work of Chilean journalist Georgina Durand, pseudonym for Raquel Delaporte Prieto (1893-?), in particular on a series of interviews published in the newspaper La Nación (Chile) in the last century in the late thirties and early forties. On the one hand, the paper analyzes the creation of biographical profiles of her interviewees as professional artists and intellectuals, conveying information to create cannons and hierarchies for emerging fields of knowledge at that time. On the other hand, attention is given to her role as interviewer and as a professional in a work and social context in which women’s participation in the public arena was still contested. In this context, it also considers the rules governing what can and cannot be said, the tensions between public and private spheres, and the potential relationship between the journalist and her readers. In the end, one could suggest that Durand achieves a balance between “correct” practice as a professional journalist, particularly in the production of her interviews, and the construction of a subjectivity.